Potential Products of Tourism in Surkhet District, Nepal - Dhakal, Aishwarya Prasad (Nepal Journal of Multidisciplinary Research, 2019)
Tourism industry plays a decisive role in the overall development of Nepal. Nepal has got a very strong power of nature because of its natural and cultural diversification. Tourism has a great role to play to improve country's image in international arena. Tourism is a driving force for the economic development of Nepal. It is a major contributor to Nepalese economy. Tourism sector is considered an answer to strengthen the national economy, improve living standard and reduce poverty. Surkhet District represents the complex cross-section of linguistics, cultural, religious, and biological diversities of the nation. It is the gate way of Karnali Province, and also connectivity with the Mansarover; the great holy place of Hindu. The resources of tourism available in Surkhet district provide decisive meaning for tourism development not only in Karnali province but also in whole Nepal. Both primary and secondary data are used to identify the potential products of tourism development. The relevancy of this study goes to have a sufficient knowledge among the stakeholders of tourism development. It has high level of potential of potential products for religious/pilgrimage tourism, rural tourism, eco-tourism, cultural tourism, village tourism, agro-tourism, adventure tourism, health tourism etc.